Análisis de consumo de energía eléctrica en la industria metálica Cotopaxi ubicada en el cantón Latacunga provincia de Cotopaxi Diseño de un plan de ahorro energético para reducir el consumo de energía. - Parreño Olmos, José Alfredo (2017)
This research work analyzes the existing electricity consumption within the COTOPAXI METALLIC INDUSTRY by means of a network analyzer, the experimental and field method was applied, which allowed to establish a problem with respect to the distribution of load by phase since They find unbalanced, high electricity consumption and a low power factor that varies between 0.6 and 0.9 in the working day.